2022
DOI: 10.1002/app.53338
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of acryloyl morpholine modified emulsion fracturing fluid thickener with high temperature resistance and salt resistance

Abstract: To prepare the thickener of fracturing fluid with temperature resistance, salt resistance and quick dissolution, an emulsion thickener (ASC) was synthesized by acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, and acryloyl morpholine. The dissolution, salt resistance and drag reduction of ASC, and the viscoelasticity, temperature resistance and shear resistance and gel breaking properties of fracturing fluid formed by ASC and zirconium crosslinker were investigated. The results showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…36 The literature also highlighted that the functional substitution other than ATBS also yielded with better %DR performance when compared to nonfunctionalized PAMs in similar conditions. 44,45,56 The observed increase in %DR in the SPAM-brine systems with the rise in sulfonic substitution (i.e., charge density) in the SPAMs of equivalent MW was in-contrast with Eshrati et al 96 ; these researchers have observed the increase in charge density, in fact, reduced the drag reduction ability of the polymers in oil-water multiphase flow systems. The %DR values of all the studied polymers in various brine systems are mentioned in Table 5.…”
Section: Flow Response Of Base Brinesmentioning
confidence: 90%
See 1 more Smart Citation
“…36 The literature also highlighted that the functional substitution other than ATBS also yielded with better %DR performance when compared to nonfunctionalized PAMs in similar conditions. 44,45,56 The observed increase in %DR in the SPAM-brine systems with the rise in sulfonic substitution (i.e., charge density) in the SPAMs of equivalent MW was in-contrast with Eshrati et al 96 ; these researchers have observed the increase in charge density, in fact, reduced the drag reduction ability of the polymers in oil-water multiphase flow systems. The %DR values of all the studied polymers in various brine systems are mentioned in Table 5.…”
Section: Flow Response Of Base Brinesmentioning
confidence: 90%
“…These salts tend to impede the %DR performance of PAMs by causing the linear structure of polymers to coil. 40 To increase salt tolerance of these polymers, chain modification with various functional group substitutions have been reported from various studies, for example, polymer substitutions with styrene, 41 acrylamide tertiary butyl sulfonic acid (ATBS), 14,33,40,42,43 triblock-polymer of polyethylene oxide (PEO), and polypropylene oxide (PPO), 44 acryloyl morpholine (ACMO) 45 have been reported in the literature. Functional substitution with ATBS comonomer during polymerization of base acrylamide monomers have also resulted in increase in the viscosity of the polymer solution in the brine systems.…”
Section: Introductionmentioning
confidence: 99%
“…Zirconium oxychloride (ZrOCl 2 ·8H 2 O, AR 98%), aluminum chloride (AlCl 3 , AR 98%), lactic acid (LA, AR 98%), ethanediamine (ESD, AR 98%), sorbitol (SOR, AR 98%), sodium chloride (NaCl, AR 99.5%), calcium chloride (CaCl 2 , AR 98%), sodium hydroxide (NaOH, AR 98%), and ammonium persulfate (APS, AR 98%) were purchased from Shanghai Aladdin BioChem Technology Co., Ltd. (Shanghai, China) The thickener (a copolymer of AM, AA, AMPS and ACMO, denoted as ASC) was synthesized in the laboratory, as depicted in Figure 10 [ 39 ]. Thickener 2 is a biopolymer; CMHPG (industrial grade, molecular weight of 1.36 × 10 6 g/mol) polymer powder is made by Shandong AK Biotech Co., Ltd., (Dongying, China) and its chemical composition is presented in Figure 11 .…”
Section: Methodsmentioning
confidence: 99%
“…Hydraulic fracturing is an effective technique for stimulating low-permeability and ultralow-permeability oil and gas reservoirs. A large amount of fracturing fluid is pumped to the bottomhole under high pressure to form the induced fractures, and the proppant is carried and transported into the fractures. The proppant located in the fractures will prevent the fractures from fully closing after fracturing operation, , resulting in a channel with permeability several orders of magnitude higher than the permeability of the formation itself. The viscosity and elastic properties of the fracturing fluid are crucial for creating the designed fracture geometry and controlling the suspension efficiency of proppants. Therefore, a reasonable selection of fracturing fluid is very important in hydraulic fracturing treatment.…”
Section: Introductionmentioning
confidence: 99%